Extração de polifenóis do bagaço de umbu-cajá (Spondias bahiensis) assistida por ultrassom para aplicação em almôndega caprina: efeitos na estabilidade oxidativa e bioacessibilidade - Silva, Anna Júllia Bezerra da (2023)
This study was carried out with the objective of optimizing the conditions for extracting polyphenols from umbu-cajá (Spondias bahiensis) bagasse by ultrasound assisted extraction, determining the phenolic profile and the antioxidant properties of the extract obtained before and after simulated in vitro digestion. Also, to evaluate the effect of incorporating this extract on the oxidative stability of pre-cooked goat meatballs during 10 days of refrigerated storage, checking the content of oxidation products after simulated digestion. A central composite rotational design (CCRD) was used to determine the optimum conditions for the hydroethanolic extraction of phenolic compounds from umbu-cajá bagasse, considering ethanol concentration, sonication time and substrate:solvent ratio. Of the 17 tests, the one with the highest levels of total phenolic compounds and antioxidant activity against the DPPH radical was subjected to analysis of the phenolic profile, antioxidant activity against the ABTS radical, iron reducing power, ferrous ion chelating activity and determination of bioaccessibility in the extract, as well as being assessed for its antioxidant capacity in vitro. The optimized phenolic extract (20 min of sonication, bagasse:solvent ratio of 1:36.8 and 55% ethanol) was applied to goat meatballs in two concentrations, EX2 being the meatball with natural extract added in a volume equivalent to 0.5 g of total extract solids/kg of product and EX4 being the meatball with natural extract added in a volume equivalent to 1.0 g of total extract solids/kg of product. Two reference treatments were prepared: control (meatball with no antioxidant added); and BHT (meatball with 0.2 g of butylated hydroxytoluene (BHT)/kg of product). The effects of the concentration of umbu-cajá extract and storage time under refrigeration (10 days) on the oxidative stability of goat meatballs were evaluated considering the parameters of moisture, pH, instrumental color, peroxide index, TBARS, carbonyl compounds. The intestinal fraction of the meatballs was evaluated for its phenolic, DPPH, ABTS, malonaldehyde and total carbonyl content. The extract showed 839.65 mg EAG of total phenolics and the antioxidant activity measured by the DPPH, ABTS and FRAP assays was 1938.0 mM Eq.T.100g-1 dw, 2681.1 mM Eq.T.100g-1 dw and 571.3 mM TE.100g-1 dw, respectively. The phenolic profile of the optimized extract revealed a predominance of gallic acid and quercetin. The majority of the phenolics identified showed high bioaccessibility, resulting in significant antioxidant activity in the intestinal fraction. The application of umbu-cajá bagasse extract in different concentrations had a positive effect on delaying lipid oxidation until day 10 and protein oxidation until day 5. However, the different concentrations of the extract were unable to inhibit color changes. The phenolic compounds showed high antioxidant capacity in vitro, as proven by the DPPH and ABTS assays, and good bioaccessibility of the phenolics. It also showed a low content of malonaldehyde and carbonyl compounds in the intestinal fraction. Therefore, the extract has a similar performance to the synthetic antioxidant used, and can partially or totally replace the synthetic preservative.